Study of the spectrum of reactivity of monoclonal antibodies to Kazakhstan isolates of influenza A virus (H1N1) (Experimental biology, 2016)
Results of the study immunological characteristics of monoclonal antibodies (mAb 5S3, 4F2, 3G4 and 2H6), received by influenza viruses A/Almaty/5/98 (H1N1) and A/Almaty/373/09 (H1N1) are presented. It was found that the MCA have a wide range of responses and reactions of hemagglutination in high titers (1: 160 - 1: 10240) inhibited the hemagglutinating activity of homologous and related reference and Kazakh influenza viruses and did not react with heterologous virus A (H3N2) and type B. reaction microneutralization ICA neutralize the virus influenza A (H1N1) and did not react with influenza A (H3N2) and B-type similar spectrum of ICA reactivity with respect to virus A/H1N1 indicate the presence in the lineup for all the studied viruses antigenic determinants, which allows recommend obtained by ICA to differentiate virus A (H1N1) strains of seasonal A (H3N2) and type B.
Keywords: monoclonal antibody; influenza virus; hemagglutinin; enzyme immunoassay; hemagglutination inhibition; reaction of micro neutralization